Menciptakan Lingkungan Belajar Aman dan Nyaman di Lembaga Pendidikan Anak Usia Dini - Putri, Habibah Afiyanti; Hibana (Institut Agama Islam Negeri Madura, 2024)
This study explores the importance of creating a safe and comfortable learning environment in early childhood education (PAUD), involving both physical and psychological aspects. A safe environment includes strong and secure buildings, first aid equipment (P3K), anti-violence policies, and the physical and psychological safety of children. The research method used is qualitative with a library research approach, examining various sources such as books, scientific articles, and important documents. The research results indicate that a safe learning environment is crucial to support the holistic development of children. Physical aspects include the security of buildings, surroundings, and first aid facilities, while psychological aspects encompass policies against physical violence, sexual abuse, and bullying. Policies and concrete steps such as implementing non-violent sanctions, positive discipline, and the involvement of parents and the community are essential to create a positive and productive learning atmosphere.